Service Distribution in IP Networks – A Business Model Analysis - Wulf, Jochen (Electronic Communications of the EASST, 2011)
In this paper we analyze different business models for the distribution ofcontent and services over IP networks and outline their distinct characteristics and valuepropositions. Four business models are distinguished: Centralized Internet Hosting, DirectHoming, Content Delivery Networks and P2P Distribution. In contrast to prior research,we focus on the ability of present technology to support distribution quality. Moreover,we discuss required value chain activities and roles, technological resources, as well asrevenue models and cost structures. Following an inductive approach, we generalize frombusiness models in practice. We present case studies in order to demonstrate, how thesebusiness models are implemented. This structured business model analysis demonstratesthe different courses of action of providers regarding the IP based distribution of theircontent and services.